Experimental Investigation on the Fracture Behaviour of Natural Stones Exposed to Monotonic and Cyclic Loading (Fracture and Structural Integrity, 2018)
The present paper is devoted to an experimental study on the fracture behaviour of natural stones, commonly used as elements for building cladding, under both monotonic and cyclic loading, with particular emphasis to white Carrara marble. The effect of progressive damage produced by in-service thermal fluctuations can be investigated through the application of appropriate cyclic mechanical loads. In the experimental tests conducted, some static mechanical properties of marble are characterized by means of three-point bending tests on edge-cracked prismatic specimens for the determination of Young's modulus, tensile strength and fracture energy. Moreover, cyclic three-point bending tests are conducted to determine the propagation rate of nominally Mode-I fatigue cracks. Finally, the fatigue behaviour of the marble is studied through a cohesive crack model, in which the direct tensile strength of the material is determined by a Brazilian test, and the behaviour is calibrated by means of a suitable FE model. The effect of crack path on the fracture resistance of marble is discussed.
Keywords: marble; quasi-brittle behaviour; thermal cycles; fatigue crack propagation